FINAL VERIFIED ENGLISH VERSION (ERROR-FREE) INFLUENCE OF HERBAL PREPARATIONS ON THE COOPERATION OF T AND B LYMPHOCYTES (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
The development of an immune response to thymus-dependent antigens, such as sheep red blood cells (SRBC), requires cooperative interactions between T and B lymphocytes. This cooperation is essential for the transformation of B cells into plasma cells—the main producers of antibodies. Therefore, assessing the effects of herbal preparations on these cooperative interactions is of considerable scientific and practical importance.